2020
DOI: 10.1177/1534734620971106
|View full text |Cite
|
Sign up to set email alerts
|

Metatarsal Head Resection Versus a Removable Mechanical Device for Offloading of the Neuropathic Diabetic Plantar Forefoot Ulcer

Abstract: Although surgical offloading seems a more permanent solution for prevention and treatment of neuropathic plantar diabetic forefoot ulcers (DFUs), the evidence for this assumption is weak and needs further studies to be established. The aim of this retrospective study is to compare the healing efficacy, associated morbidity, and recurrence rates of surgical versus removable knee-high offloading for neuropathic plantar (DFUs) healing. From January 2016 to January 2018, 70 neuropathic plantar forefoot DFUs were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…11,19 Over the past 4 years, a number of new trials have been performed in the area of offloading that add to the evidence base for treating people with DFU. [23][24][25][26][27][28][29] Ulcer healing is still recognised as the key critically important outcome for people with DFU. However, other outcomes of importance to people with DFU are receiving more attention and also require careful consideration when developing recommendations in new offloading guidelines, such as effects on plantar pressure, weight-bearing activity, adherence, adverse effects, quality of life, and costs.…”
Section: A)mentioning
confidence: 99%
“…11,19 Over the past 4 years, a number of new trials have been performed in the area of offloading that add to the evidence base for treating people with DFU. [23][24][25][26][27][28][29] Ulcer healing is still recognised as the key critically important outcome for people with DFU. However, other outcomes of importance to people with DFU are receiving more attention and also require careful consideration when developing recommendations in new offloading guidelines, such as effects on plantar pressure, weight-bearing activity, adherence, adverse effects, quality of life, and costs.…”
Section: A)mentioning
confidence: 99%
“…See the Comparison 7 SoF tables and forest plots in Supplementary File S2. Note as there was controlled study evidence for six different surgical offloading interventions, we reviewed each separately and produced six SoF tables for this comparison, including Achilles tendon lengthening 81,82,[114][115][116][117][118] (Comparison 7A), metatarsal head resections 34,83,91,93,94,[119][120][121][122][123][124][125] (Comparison 7B), joint arthroplasties 95,96,[126][127][128][129] (Comparison 7C), joint arthrodeses 80 (Comparison 7D), metatarsal osteotomies 92,[130][131][132][133][134] (Comparison 7E), and digital flexor tenotomies 36,50,51,[135][136][137][138][139][140][141][142][143][144][145] (Comparison 7F...…”
Section: Comparisons 7: Surgical Offloading Interventions Versus Non-...mentioning
confidence: 99%
“…Ulcers healed Meta-analysis of 3 studies (1 RCT, 83 2 other controlled studies 34,91 ), and 2 other controlled studies reporting similar findings that could not be pooled 93,94 and 7 non-controlled studies, [119][120][121][122][123][124][125] found metatarsal head resection (MHR) with offloading devices or therapeutic footwear versus devices or footwear alone may cause moderate increases in proportions of ulcers healed (RR 1.33, 1.12-1.58; p = 0.001; I 2 = 23%; N = 3; n = 165; Low CoE).…”
Section: Critical Outcomementioning
confidence: 99%
See 2 more Smart Citations